2009
DOI: 10.1159/000206142
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Organizational Content of Clinical Pathways for Digestive Surgery: A Systematic Review

Abstract: Background/Aims: Oncology surgery of the gastrointestinal tract is complex and infamous for its high complication rates. One of the methods for implementing interventions to optimize the patients’ condition and to enhance postoperative outcome is the development and implementation of a clinical pathway. The aim of this study was to analyze the content, i.e. the interventions of clinical pathways for digestive surgery and their effects on postoperative outcome measures. Methods: We performed a systematic review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 73 publications
1
57
0
Order By: Relevance
“…41 Relative to being used successfully and maturely in colorectal surgery, FT programs are performed infrequently in other types of surgery such as hepatic resection.…”
Section: Discussionmentioning
confidence: 99%
“…41 Relative to being used successfully and maturely in colorectal surgery, FT programs are performed infrequently in other types of surgery such as hepatic resection.…”
Section: Discussionmentioning
confidence: 99%
“…2 Enhanced recovery after surgery (ERAS) is associated with a shortened hospital stay and minimal morbidity. [4][5][6][7] A meta-analysis of surgically placed wound catheters (SPWCs) for the management of postoperative pain after breast surgery looked at 4 randomised controlled trials (RCTs) including a total of 147 women. 8 This study showed a trend towards improved pain control.…”
Section: Discussionmentioning
confidence: 99%
“…These process improvement tools have gained popularity in many different surgical settings [24][25][26][27] . Most have been developed and implemented at an institutional level 24 .…”
Section: Discussionmentioning
confidence: 99%